Deiksis Dialek Bugis dan Makassar Kecamatan Sangkarrang Kelurahan Barrang Caddi Kota Makassar - Fitriani, Fitriani; Razak, Nur Khadijah; Anzar, Anzar (Nuances of Indonesian Language, 2023)
This study aims to describe the deixis usage of the Makassar and Bugis dialects in Makassar City, Barrang Caddi Village, and Sangkarrang District. This study employed a descriptive-qualitative methodology. Based on the collected data, it was discovered that both dialects are used in society, and that both pay close attention to the degree of politeness when speaking, particularly to elder speech partners. Additionally, there will be variations in the usage of deixis between speech partners if they belong to different social classes or societal levels, such as those descended from the aristocracy. Five deixis—persona deixis (first singular, plural, second singular, second plural, third)—show distinctions between the usage of Bugis and Makassar deixis.